A Novel Method to Improve Health Risk Assessment Using Bio-accessible Arsenic in Rice Grain Grown in Contaminated Soils - Raza, Md. Basit; Datta, Siba P.; Golui, Debasis; Barman, Mandira; Ray, Prasenjit (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during kharif (June to September) of 2020 at the net house facility in Division of Soil Science and Agricultural Chemistry, ICAR-Indian Agricultural Research Institute, New Delhi, India which evaluated the efficacy of organic amendments, specifically sugarcane bagasse, and vermicompost, in mitigating soil As contamination and reducing its uptake by rice crop. Furthermore, the human health risk assessment protocol was refined and improved to prevent its over-estimation using bio-accessible grain As content. Sugarcane bagasse enhanced SOC and reduced Olsen-As compared to vermicompost. The rice grain As content, although below the Codex safe limit of 0.2 mg kg-1, varied proportionally with soil Olsen-As. The bioaccessibility of As in rice grains, determined using in-vitro gastrointestinal method, ranged from 67% to 69% of the total grain As. Health risk assessments using bio-accessible As highlighted non-cancer risks (HQ>1) for both adults and children, suggesting a potential health concern upon continued rice consumption grown in these soils. Despite this, the severity-adjusted margin of exposure (SAMOE) values categorized cancer risk as low. Among both the amendments, sugarcane bagasse demonstrated superior efficacy in reducing soil and plant As levels. The findings underscore the potential of organic amendments, particularly sugarcane bagasse, in improving soil quality and reducing As bioavailability. Using bioaccessible As content instead of total rice grain As content can essentially improve the accuracy and reliability of health risk assessments.